Efektivitas Sistem Pengendalian Intern dalam Meningkatkan Kinerja Keuangan pada Perusahaan Umum Daerah Air Minum Mual Nauli Kabupaten Tapanuli Tengah - Megawati Sitompul; Deliana Deliana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the effectiveness of the internal control system in improving financial performance at the Regional Public Company (Perumda) Mual Nauli Drinking Water of Central Tapanuli Regency. The research used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation for five months. The results showed that although the Internal Supervisory Unit (SPI) has played an effective role in overseeing operational activities, its contribution to financial supervision is still limited due to a lack of understanding of financial statements. As a result, the company's financial performance has fluctuated and has not reached an optimal level. Nevertheless, SPI has tried to reduce operational inefficiencies and prevent irregularities. These findings emphasize the importance of improving SPI's financial competence and strengthening audit procedures to support transparent and accountable financial management.